Alice-Miranda at school - Harvey, Jacqueline (Australia Random house Australia, 2010)
Alice-Miranda Highton-Smith-Kennigton-Jones can't wait to start boarding school. When she arrives at Winchesterfield-Downsfordvale Academy for Proper Young Ladies, the adventure begins ... only not quite as Alice-Miranda expects. The minute she sets foot on the school's manicured grounds, she senses that something is wrong: Miss Grimm, the headmistress, is nowhere to be seen, the gardens have no flowers, and a mysterious stranger seems to be hiding out on the premises.
Keywords: Schools -- Boarding schools -- Detective and mystery stories